Differences between Internal Jugular Vein and Vertebral Vein Flow Examined in Real Time with the Use of Multigate Ultrasound Color Doppler - Ciuti, G.; Righi, D.; Forzoni, L.; Fabbri, A.; Pignone, A. Moggi (American Journal of Neuroradiology, 2013)
BACKGROUND AND PURPOSE: The hypothesis that MS could be provoked by a derangement of the blood outflow from the brain has been largely discredited. In part, it was because data on the normal pattern of outflow are scarce and obtained with different methods. The aim of this study was to evaluate the normal pattern of outflow for the vertebral and internal jugular veins in healthy subjects with multigate color Doppler. MATERIALS AND METHODS: Twenty-five volunteers were studied to assess vessel area, mean velocity, and flow for the vertebral and internal jugular veins in the supine and sitting positions. RESULTS: In the sitting position, flow decreases, both in vertebral veins and internal jugular veins, as the total vessel area decreases (from 0.46 ± 0.57 to 0.09 ± 0.08 cm2), even if the mean velocity increases (from 12.58 ± 10.19 to 24.14 ± 17.60 cm/s). Contrary to what happens to the blood inflow, outflow in the supine position, through vertebral and internal jugular veins, is more than twice the outflow in the sitting position (739.80 ± 326.32 versus 278.24 ± 207.94 mL/min). In the sitting position, on application of very low pressure to the skin with the sonography probe, internal jugular veins rarely appear to occlude. A pronounced difference of diameter between internal jugular veins was present in approximately one-third of subjects. CONCLUSIONS: Our results support the view that other outflow pathways, like the vertebral plexus, play a major role in the normal physiology of brain circulation and must be assessed to obtain a complete picture of blood outflow. VVvertebral veinIJVinternal jugular veinBFblood flowQDPQuality Doppler Profiles